2016
DOI: 10.1016/j.jcma.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Visual prognosis of massive submacular hemorrhage in polypoidal choroidal vasculopathy with or without combination treatment

Abstract: Combination treatment of submacular hemorrhage secondary to PCV may yield visual and anatomic improvements. Initial BCVA, the initial size of submacular hemorrhage and age were significant predictors for visual prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Figure 1 shows that data obtained from 17 [ 10 , 12 – 17 , 19 , 20 , 22 , 23 , 25 , 26 , 28 – 31 ] related studies ( n = 966) could be combined. Using the random effect model for data combination, results revealed that the level of fasting blood glucose in the Qigong group was lower than that in the nonexercise group, and the difference was statistically significant (MD = −0.99, 95% CI [−1.23, −0.75], P < 0.00001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows that data obtained from 17 [ 10 , 12 – 17 , 19 , 20 , 22 , 23 , 25 , 26 , 28 – 31 ] related studies ( n = 966) could be combined. Using the random effect model for data combination, results revealed that the level of fasting blood glucose in the Qigong group was lower than that in the nonexercise group, and the difference was statistically significant (MD = −0.99, 95% CI [−1.23, −0.75], P < 0.00001).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows that the data obtained from five [ 10 , 26 – 28 , 31 ] related studies ( n = 389) can be summarized. Using the random effect model for data combination, results revealed that there was no statistically significant difference between the Qigong group and the other aerobic exercise groups (MD = −0.67, 95% CI, [−1.42,0.07], P = 0.07).…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature on the role of vitrectomy for subretinal bleed in PCV is scarce. 160162 Pars plana vitrectomy with a subretinal administration of rtPA (50 μg) and pneumatic displacement by intravitreal gas with short-term facedown positioning can help in near complete displacement and resolution of submacular bleeds. Furthermore, it also allows early treatment of the polypoidal lesions by PDT with or without anti-VEGF injection.…”
Section: Surgical Management For Submacular Haemorrhagementioning
confidence: 99%
“…In a prospective study of 20 PCV cases with submacular haemorrhage, who received either subretinal tissue plasminogen activator (tPA) with vitrectomy or intravitreal injection of tPA and gas, visual and anatomical results were better in the vitrectomy arm. 162 Vitrectomy may also be needed in cases with breakthrough vitreous haemorrhage, which may be de novo or following intervention like PDT/pneumatic displacement.…”
Section: Surgical Management For Submacular Haemorrhagementioning
confidence: 99%
“…Polyps that remain patent may bleed or leak, which results in worsening of VA. 13 In addition, some cases may develop large subretinal hemorrhages ( Figure 2), often termed as "massive submacular hemorrhage," which may be associated with a poor prognosis and result in significant visual loss. [13][14][15]…”
Section: Practical Retinamentioning
confidence: 99%